Pengaruh Kesadaran Merek dan Citra Merek terhadap Loyalitas Pelanggan (Studi pada Pelanggan Teh Pucuk Harum Wilayah Surabaya Utara) - Andjarwati, Anik Lestari; Chusniartiningsih, Eka (Jurnal Minds: Manajemen Ide dan Inspirasi, 2018)
The purpose of this study is to examine and analyze the effect of brand awareness and brand image to customer loyalty on customer of Teh Pucuk Harum. This research is a causality research with quantitative approach. Technique of sampling using non probability sampling with amount 220 respondents in North Surabaya. Statistical analysis in this study is multiple linier regresiom with the help of SPSS 22.0 software. The results of this study explain that brand awareness had a positive and significant effect on the customer loyalty, and brand image had a positive and significant effect on the customer loyalty.